Financial literacy and financial behavior: Evidence from the emerging Asian middle class - Antonia Grohmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper analyses financial literacy and financial behavior of middle class people living an urban Asian economy. Other than most papers on financial literacy that focus on people in developed countries, we surveyed people living Bangkok. Using standard financial literacy questions, we find that financial literacy levels are largely comparable to industrialized countries, but understanding of more advanced financial concepts is lower. Similarly, savings accounts are held by most people, but more sophisticated products are a lot less common. We further show, in line with the literature, that higher financial literacy leads to improved financial decision making.
Keywords: D14; G11; D91; 330; Financial literacy; Saving; Borrowing; Household finance